Understanding the Notion of »Ecosystem Approach« - Vovk Korže, Ana (Journal for Geography, 2008)
Ecosystem modifications are caused by anthropogenic activities. Human adaptation to the changes within the ecosystem is slow, because it all starts by changing awareness, values, utilization patterns, knowledge accumulation and good practice examples. Social components of the ecosystem (technological and institutional) can be quick and outmatch modification capacities of other parts of the ecosystem. For example, rapid consumption of natural resources exceeds their restoration. So it is necessary to choose a more responsible attitude towards natural resources, ecosystem assets and services.
Keywords: ecosystem approach; sustainable development; ecoremediation; geography; natural resources